ChemInform Abstract: Catalytic Asymmetric Reactions of 4‐Substituted Indoles with Nitroethene: A Direct Entry to Ergot Alkaloid Structures. Issue 18 (April 2016) - Romanini, Simone; Galletti, Emilio; Caruana, Lorenzo; Mazzanti, Andrea; Himo, Fahmi; Santoro, Stefano; Fochi, Mariafrancesca; Bernardi, Luca
Abstract: The utility of this method is demonstrated in the synthesis of compound (VII) which can be further converted to the alkaloid 6, 7‐secoagroclavine.